REMAJA DAN BIMBINGAN KONSELING - Ninil Elfira (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2017)
Teenagers are individuals in a state of unstable because of a change from childhood to the adult state. Such situation causes these individuals have difficulty in adapting to the environment. In fact, this condition causes the adolescent experience deviant behavior. Teens who do this deviant's behavior needs serious attention from all parties. One of the professional activities that can help teens cope with deviant behavior is counseling. This counseling is done by professionals that counselors.